Shell-like Structures Advanced Theories and Applications - Altenbach, Holm.; Eremeyev, Victor; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The book presents mathematical and mechanical aspects of the theory of plates and shells, applications in civil, aero-space and mechanical engineering, as well in other areas. The focus relates to the following problems: • comprehensive review of the most popular theories of plates and shells, • relations between three-dimensional theories and two-dimensional ones, • presentation of recently developed new refined plates and shells theories (for example, the micropolar theory or gradient-type theories), • modeling of coupled effects in shells and plates related to electromagnetic and temperature fields, phase transitions, diffusion, etc., • applications in modeling of non-classical objects like, for example, nanostructures, • presentation of actual numerical tools based on the finite element approach.
Thin-walled structural elements: classification, classical and advanced theories, new applications -- Basics of mechanics of micropolar shells -- The bending-gradient theory for laminates and in-plane periodic plates -- Some problems on localized vibrations and waves in thin shells -- Six lectures in the mechanics of elastic structures -- Selected topics on mixed/enhanced four-node shell elements with drilling rotation.
Keywords: Mechanics, Applied; Solids; Civil engineering; Solid Mechanics; Civil Engineering